Hochdruck-Blechumformung mit formlos festen Stoffen als Wirkmedium - Grüner, Martin (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2014)
Using small ceramic spheres as forming medium for blank hydroforming processes allows combining benefits of hydroforming and warm forming of ultra high strength steel. Especially the advantageous leakage behavior of granular material compared to gases and fluids allows a significant reduction of blankholder forces and thereby an increase in moldin